Contrasting acclimation abilities of two dominant boreal conifers to elevated CO2 and temperature. (30th March 2018) - Kurepin, Leonid V.; Stangl, Zsofia R.; Ivanov, Alexander G.; Bui, Vi; Mema, Marin; Hüner, Norman P.A.; Öquist, Gunnar; Way, Danielle; Hurry, Vaughan
Abstract: High latitude forests will experience large changes in temperature and CO2 concentrations this century. We evaluated the effects of future climate conditions on 2 dominant boreal tree species, Pinus sylvestris L. and Picea abies (L.) H. Karst, exposing seedlings to 3 seasons of ambient (430 ppm) or elevated CO2 (750 ppm) and ambient temperatures, a + 4 °C warming or a + 8 °C warming. Pinus sylvestris responded positively to warming: seedlings developed a larger canopy, maintained high net CO2 assimilation rates (Anet ), and acclimated dark respiration (Rdark ). In contrast, carbon fluxes in Picea abies were negatively impacted by warming: maximum rates of Anet decreased, electron transport was redirected to alternative electron acceptors, and thermal acclimation of Rdark was weak. Elevated CO2 tended to exacerbate these effects in warm‐grown Picea abies, and by the end of the experiment Picea abies from the +8 °C, high CO2 treatment produced fewer buds than they had 3 years earlier. Treatments had little effect on leaf and wood anatomy. Our results highlight that species within the same plant functional type may show opposite responses to warming and imply that Picea abies may be particularly vulnerable to warming due to low plasticity in photosynthetic and respiratory metabolism. Abstract : We investigated whether two common boreal tree species from the same plant functional type showed similar responses to growth under a range of future climate scenarios, including elevated CO2 and temperatures. Although Scots pine acclimated to the treatments, enabling this species to maintain high photosynthetic rates and to reduce respiratory costs under warming and high CO2 treatments, Norway spruce showed little capacity for acclimation, such that high temperatures reduced photosynthetic performance. Our results demonstrate that we cannot assume that species form the same plant functional type will necessarily respond in similar manners to future climate change and highlight the need to understand the mechanisms allowing species to acclimate successfully to elevated temperatures and CO2 concentrations.